(untitled) (Scottish Archaeological Internet Reports, 2009)
The Applecross peninsula was visited on a number of occasions during the course of the project in order to record present vegetation and soil conditions in the hope that these might throw light on the environmental history of the area. Settlement along the peninsula appears to have been restricted through time to a narrow elevational band, which the topography has confined to within about a kilometre of the modern shoreline. Exploitation of the inland areas is likely to have been limited to seasonal grazing and hunting. This section therefore concentrates on the coastal fringe. The climate, geology, soils and vegetation of the present day are all examined and the final discussion looks at the changes within these over the Holocene.